TETRAPLEURA TETRAPTERA: MOLLUSCICIDAL ACTIVITY AND CHEMICAL CONSTITUENTS - Aladesanmi, Adetunji J. (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
Tetrapleura tetraptera (Schumach. And Thonn) Taub, Mimosaceae, commonly known as Aridan (fruit), A single stemmed, robust, perennial tree of about 30m.It has a grey/brown, smooth/rough bark with glabrous yound branchlets. The flower is yellow/pink and racemes white the fruit has dark brown, four winged pods 12-25 x 3.5-6.5cm.It is generally found in the lowland forest of tropical Africa. The fruit consists of a fleshy pulp with small, brownish-black seeds. The fruit possesses a fragrants, characteristically pungent aromatic odour, which is attributed to its insect repellent property. It is used as spices and aroma (exotic tropical scents) and fish poisoning. It is one of the molluscicidal medicinal plants of Nigeria, also useful in the management of convulsions, leprosy, inflammation and/or rheumatoid pains. The documented biological and-or pharmacological activities are found to be molluscicidal, cardio-vascular, neuromuscular, hypotensive, anti-convulsant, molluscicidal, trypanocidal, hirudinicidal, schistomiasis control, anti-ulcerative, ectoxicity, anti-inflammatory, hypoglycaemic, anti-microbial, emulsifying property, birth control, food value and the control of intestinal parasites. Activity-guided fractionation of the methanol extract of the fruits of T. Tetraptera led to the isolation of a saponin glycoside with an oleanolic acid aglycone, a monodesmosidic diglycoside of the rare sapogenin 27-hydroxyolean-12 (13)-en-28-oic acid; echinocystic acid-3-0-sodium sulfate from the stembark, umbelliferone and ferulic acid from the leaves and branches respectively. Also isolated from the fruits were aridanin and three of its olean-12-en-28-oic acid derivatives. All the compounds isolated either from the fruits or other parts were found to exhibit strong molluscicidal properties against the schistosomiasis-transmitting snails Biomphalaria glabrata.